The Efficacy and Safety of Avanafil During a Treatment of Male Erectile Dysfunction: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Warli SM; Steven S; Kadar DD; Prapiska FF; Siregar GP (Dove Medical Press, 2023)
Syah Mirsya Warli,1,2 Steven Steven,3 Dhirajaya Dharma Kadar,1 Fauriski Febrian Prapiska,1 Ginanda Putra Siregar1 1Division of Urology, Department of Surgery, Faculty of Medicine, Universitas Sumatera Utara - Haji Adam Malik General Hospital, Medan, Indonesia; 2Department of Urology, Universitas Sumatera Utara Hospital, Universitas Sumatera Utara, Medan, Indonesia; 3Department of Urology, Faculty of Medicine, Universitas Indonesia - Haji Adam Malik General Hospital, Medan, IndonesiaCorrespondence: Syah Mirsya Warli, Division of Urology, Department of Surgery, Faculty of Medicine, Universitas Sumatera Utara, Dr. Mansyur No. 5 Medan, North Sumatera, 20154, Indonesia, Tel +6261-8364930, Email warli@usu.ac.idPurpose: Erectile dysfunction (ED) contributes to a large burden and impairs the quality of life among males. Avanafil appears to be a promising treatment for ED; however, its efficacy and safety profile remain unclear. This study aimed to evaluate the efficacy and safety of avanafil for the treatment of ED.Patients and Methods: An extensive search of PubMed, ScienceDirect, Web of Science, and Embase databases with 11 publications was performed, with outcomes evaluated are International Index of Erectile Function - Erectile Function (IIEF-EF), Sexual Encounter Profile (SEP), and Treatment-Emergent Adverse Events (TEAE). Statistical parameter Mean Difference (MD) and Risk Ratio (RR) with 95% Confidence Interval (CI) were used to measure effect size.Results: The pooled estimates demonstrated that changes in IIEF-EF function (MD=4.39, 95% CI [3.41, 5.37], p< 0.001), SEP-2 (RR=3.43, 95% CI [2.79, 4.22], p< 0.001), SEP-3 (RR=2.30, 95% CI [2.01, 2.62], p< 0.001), and TEAE (RR=1.49, 95% CI [1.12, 1.96], p=0.005) were significantly higher in the avanafil group than in the placebo group. Moreover, 200 mg avanafil was superior to that mg 100 mg-avanafil, indicated by the IIEF-EF score (MD=− 1.15, 95% CI [− 1.40, − 0.89], p< 0.001). In contrary, there were no significant differences in SEP-2 (RR=0.90, 95% CI [0.75, 1.08], p=0.26), SEP-3 (RR=0.92, 95% CI [0.81, 1.05], p=0.21) and TEAE (RR=1.00, 95% CI [0.87, 1.15], p=0.99) for both 100 mg and 200 mg doses.Conclusion: This review highlights the potential use of this drug in ED treatment. Further large-scale Randomized Controlled Trials investigations involving various racial groups are required to confirm these findings.Graphical Abstract: Keywords: avanafil, erectile dysfunction, meta-analysis, systematic review, randomized controlled trial